Family office: organizational structure of household wealth management (Revista Brasileira de Contabilidade e Gestão, 2014)
This paper reviewed publications about the family offices subject (organizational structures that manage the family wealth and provide all kinds of services for these families). This organizational structure can be used as part of the family governance plan. Family offices appeared initially to assist families in managing the product generated by the business: wealth. Currently, family offices can provide all kind of professional service. The results found by the analysis indicate that there are few scientific researches on family office, both international and nationwide. We analyzed a sample of 37 (thirty-seven) articles, of which 32 (thirty two) of them are international and five (5) are national authorship. The articles were written from 2001 to 2011. There is a predominance of opinionative researches (no scientific rigor) covering 70% (seventy percent) of the sample. Only 5% (five percent) presents a empirical approach. These results demonstrate that there is a gap to be filled with empirical research on family office both in Brazil and abroad.
Keywords: family office; family governance; governance